2009
DOI: 10.1111/j.1524-4741.2009.00762.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the Cell Cycle Regulators Cyclin D1, Cyclin A, p27, p21, p16, and pRb in Apocrine Metaplasia of the Breast

Abstract: G1/S transition defects have been a proposed requirement for tumor development. Apocrine metaplasia (APM) in the breast has been held as a sign of benignity. Yet, a number of studies have reported the presence of molecular abnormalities in some forms of APM suggesting a possible oncogenic potential for some of these lesions. We currently investigate the role of some of the cell cycle proteins, previously reported to be de-regulated in breast cancer, in an attempt to assess their significance in APM. Using immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 40 publications
(52 reference statements)
1
11
0
Order By: Relevance
“…For ER-α, PR, AR, cyclin D1, p53, p63 and topoisomerase-IIα expression, only nuclear labeling was scored (24,25). For Her-2/neu and EGFR proteins, only membranous staining was considered positive.…”
Section: Methodsmentioning
confidence: 99%
“…For ER-α, PR, AR, cyclin D1, p53, p63 and topoisomerase-IIα expression, only nuclear labeling was scored (24,25). For Her-2/neu and EGFR proteins, only membranous staining was considered positive.…”
Section: Methodsmentioning
confidence: 99%
“…Wells et al [34] studied apocrine adenosis and suggested an association between apocrine adenosis, apocrine DIN, and invasive apocrine cancers based upon HER2 overexpression, nuclear p53 staining, and a high Ki-67-based proliferation index. El-Ayat G et al [7] studied Ki-67 and the cellcycle-regulating proteins cyclin D1 and pRb in apocrine metaplasia and found a significantly higher Ki-67 index and more indications of cell cycle deregulation in apocrine lesions with papillary/proliferative features than in apocrine lesions without papillary/proliferative features. The authors concluded that histologically more complex lesions are associated with significant increase of proliferative capacity and alterations of cell cycle control.…”
Section: Discussionmentioning
confidence: 97%
“…N total indicates the total number of lesions included in the study, but due to disappearance of the lesions on some slides, and limited number of slides available for staining, the number of stained lesions within each column may be smaller than N total a Not qualifying for DIN1c-3. Includes atypical apocrine metaplasia/ atypical apocrine hyperplasia and apocrine papillomas with DIN1b explored immunohistochemical markers related to tumor progression in proliferative and non-proliferative apocrine lesions [5][6][7]34]. Wells et al [34] studied apocrine adenosis and suggested an association between apocrine adenosis, apocrine DIN, and invasive apocrine cancers based upon HER2 overexpression, nuclear p53 staining, and a high Ki-67-based proliferation index.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Accordingly, we have identified a number of apocrine protein markers that include 15-prostaglandin dehydrogenase (15-PGDH) and acyl-CoA synthetase medium-chain family member 1 (ACSM1) which together with a set of categorizing markers that are predominantly expressed (AR, CD24) or not expressed (bcl-2, GATA-3) by apocrine metaplastic lesions in benign breast lesions, were proven to be specific for both apocrine ductal carcinoma in situ (ADCIS) and IAC [2], [16], [17], [19], [20]. This apocrine signature has been shown to identify unambiguously 13 out of 14 ADCIS (92.9%) and 20 out of 33 (60.6%) IACs in a well characterized set of apocrine carcinomas [2] in which more than 90% of the tumor cells exhibited cytological features typical of apocrine cells [21].…”
Section: Introductionmentioning
confidence: 99%